How farmers can adapt to a warming world - Vermeulen, Sonja J.; Challinor, Andrew J. (2013)
Global temperatures have not been this high in at least 4,000 years. The concentration of carbon dioxide in the atmosphere today - 400 parts per million - has not been this high for three million years. Climate change has moved from an abstract concept to a basic fact of nature, and scientists have been researching its effects on food production and prices. The long-range forecasts are bleak, especially in developing countries. By 2050, climate change could cause irrigated wheat yields in some regions to fall by as much as 13 percent. Irrigated rice production could tumble 15 percent on average. In some parts of Africa, farmers growing maize could lose 10 to 20 percent of their crop. It has been too easy for policy makers to seize upon the complexities of climate science as an excuse to avoid its realities, even as global food prices prove to be as volatile as the weather. However, we now have the tools and knowledge needed to act and make solid decisions. A growing number of governments have grasped the magnitude of the problem and are working to ensure their farmers can handle the continuing evolution of our planet’s seasons.